Factors influencing men’s decisions about a career in nursing - Angela V. Flynn; Oisín Brenock; Mohammad M. Saab (PLoS ONE, 2025)
Background Despite many efforts to diversify the nursing workforce, in most countries the profession remains predominantly feminine. It is widely accepted that with a greater gender balance, nursing would be better understood, would provide more holistic care, may achieve greater professional acknowledgement, and may achieve higher levels of remuneration. To address this imbalance, it is worth uncovering the factors which influence the career decision making of young men. Objectives To capture the views of men in nursing and explore the opinions of secondary school students to understand their decision-making regarding nursing as a career choice, and the factors that influence those decisions. Design Cross-sectional survey. Setting Recruitment was primarily through social media and e-mails to students, graduates, colleagues, and professional nursing and academic networks. Participants Convenience and snowball sampling strategies were used to recruit men aged 18 or above in secondary schools (Cohort 1), and men aged 18 or above who were already employed as nurses or were undergoing a nurse education programme (Cohort 2). Methods Online surveys comprising Likert scale and open-ended questions were completed. Quantitative data were analysed using descriptive statistics. Qualitative data were used to support and add depth to the quantitative findings. Illustrative participant excerpts were used to support the findings. Results A total of 130 surveys were completed. Our findings show that factors such as gender-based stereotypes and portrayals of nursing in media, are the least influencing factors that impacted on men choosing a career in nursing. In fact, the two most influential factors were found to be contact with nurses and experience with healthcare related activities such as volunteering/first aid. Conclusions Findings illustrate the influential role that all nurses have in encouraging men into a career in nursing. The findings also have implications for the allocation of resources towards recruitment and career information strategies.